Prioritization Of Administrations To Connect To The Internal Network With A Multiple Criteria Decision Making Approach (Case Study: Information Technology Administration Of Iran) - Movahedy, Somayeh (The Turkish Online Journal of Design Art and Communication, 2016)
The internal network consists of communication substructures, governmental and nongovernmental developed data centers and software substructures that have been expanded across the nation. This network provides the required capacity for “maintenance and exchange of local information in the nation for electronic services development” and “access of internet” through nationwide bandwidth connecting bed for home users, businesses and executive administrations. This network integrates specialized, local and national networks in the country, consisting of two private and public sectors. The private sector is to connect and to exchange information and services between the executive administrations and private sector, providing the required services for general users. These two sectors join each other at such points as data centers. The problem of this research is the fact that since many national administrations have a number of access points and that all administrations must join this network within the next five years, and that identifying information technology indices such as existing points, connected to national headquarters and number of existing points, connected to provincial and city offices and number of existing and connected points of associated businesses for executive administrations of the nation is of great importance for materialization of an electronic government in the nation, in this research, we have been determined to prioritize the aforesaid factors and indices. The research method is of descriptive mathematical type and the technique used is TOPSIS. Moreover, the names of ministries have not been given herein this survey.
Keywords: National Information Network; TOPSIS and Connection Points